Opioid Prescription Patterns for Children Following Laparoscopic Appendectomy. Issue 6 (December 2020) - Sonderman, Kristin A.; Wolf, Lindsey L.; Madenci, Arin L.; Kwon, Nicollette K.; Armstrong, Lindsey B.; Wanis, Kerollos Nashat; Taylor, Kathryn; Uribe-Leitz, Tarsicio; Koehlmoos, Tracey P.; Ricca, Robert L.; Weil, Brent R.; Weldon, Christopher B.; et al.
Abstract : Objective: To describe variability in and consequences of opioid prescriptions following pediatric laparoscopic appendectomy. Summary Background Data: Postoperative opioid prescribing patterns may contribute to persistent opioid use in both adults and children. Methods: We included children <18 years enrolled as dependents in the Military Health System Data Repository who underwent uncomplicated laparoscopic appendectomy (2006–2014). For the primary outcome of days of opioids prescribed, we evaluated associations with discharging service, standardized to the distribution of baseline covariates. Secondary outcomes included refill, Emergency Department (ED) visit for constipation, and ED visit for pain. Results: Among 6732 children, 68% were prescribed opioids (range = 1–65 d, median = 4 d, IQR = 3–5 d). Patients discharged by general surgery services were prescribed 1.23 (95% CI = 1.06–1.42) excess days of opioids, compared with those discharged by pediatric surgery services. Risk of ED visit for constipation (n = 61, 1%) was increased with opioid prescription [1–3 d, risk ratio (RR) = 2.46, 95% CI = 1.31–5.78; 4–6 d, RR = 1.89, 95% CI = 0.83–4.67; 7–14 d, RR = 3.75, 95% CI = 1.38–9.44; >14 d, RR = 6.27, 95% CI = 1.23–19.68], compared with no opioid prescription. There was similar or increased risk of ED visit for pain (n = 319, 5%) with opioid prescription [1–3 d, RR = 1.00, 95% confidence interval (CI) = 0.74–1.32; 4–6 d, RR = 1.31, 95% CI = 0.99–1.73; 7–14 d, RR = 1.52, 95% CI = 1.00–2.18], compared with no opioid prescription. Likewise, need for refill (n = 157, 3%) was not associated with initial days of opioid prescribed (reference 1–3 d; 4–6 d, RR = 0.96, 95% CI = 0.68–1.35; 7–14 d, RR = 0.91, 95% CI = 0.49–1.46; and >14 d, RR = 1.22, 95% CI = 0.59–2.07). Conclusions: There was substantial variation in opioid prescribing patterns. Opioid prescription duration increased risk of ED visits for constipation, but not for pain or refill. Abstract : Supplemental Digital Content is available in the text